The KARAKTERISTIK KLINIKOPATHOLOGI BERDASARKAN LOKASI KANKER KOLOREKTAL DI RUMAH SAKIT BETHESDA, YOGYAKARTA: - - Elbert Hansyah Wibowo Wibowo (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Colorectal cancer has prevalence about 10% of all cancer that can cause death. Incident number of colorectal cancer in the US in 2021 about 104.270 colon cancer cases and 45.230 rectal cancer cases with death number was 52.980 lives. There were 1.544 patients diagnosed with colorectal cancer in RSUP Dr. Sarjito between year 2008-2017 among of them 820 male and 724 female. This research used retrospective descriptive using medical record data of colorectal cancer patients between year 2016-2020, and data were analyzed using univariat and were displayed in the form of tabel and diagram. This research used research variables, including: location of colorectal cancer, stage, age, gender, histopathological picture, and clinical symptoms. Colorectal cancer There were a total of 60 patients with details of right colorectal cancer patients being male (5 patients), moderate age range (4 patients), stages 3 and 4 (2 patients each), histopathological type of adenocarcinoma (4 patients), and symptoms clinical abdominal pain (4 patients). The most common colorectal cancer is left colorectal cancer, with male gender, 40-64 years old, histopathological type of adenocarcinoma, and stage 4.